Tracing the drivers of waste generation in Poland (2010–2018): a structural decomposition and input–output approach - Gacek, Kamil (Bulletin of Geography. Socio-economic Series, 2024)
The paper discusses the application of Structural Decomposition Analysis (SDA) in an extended input-output model to trace main sources of waste generation in Poland between 2010 and 2018. Poland is a country that has experienced significant economic growth in recent years, but this growth has also led to a corresponding increase in waste generation. The economy relies on sectors and their production, generating waste in quantities that depend on various factors. SDA, as a quantitative method, can be used to examine the drivers of this waste generation. It provides insights into how changes in final demand and technology have affected the amount of waste generated by sectors over the analyzed period of time. Analyzing the results of the proposed model allows policymakers to develop targeted interventions to reduce waste and promote sustainable development. The paper concludes that this technique can be a valuable tool for environmental analysis, providing a comprehensive view of the connections between economic activity, environmental impacts and waste generation.